(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of inflatable penile prosthesis (IPP) implantation focusing on surgical efficacy, complication rates, and satisfaction of patients and their partners. Methods: A prospective descriptive case series of 30 patients who underwent primary IPP implantation for erectile dysfunction at 115 People’s Hospital from July 2019 to March 2026. Satisfaction was assessed using QoLSPP questionnaires. Results: The mean age of the patients was 56.63 ± 13.36 years. Device functionality was optimal in 100% of cases, with a mean operative time of 87.33 minutes. There were no intraoperative complications. The postoperative complication rate was 10% (3 cases), comprising 1 instance of bleeding and 2 cases of postoperative fever, all managed successfully with medical treatment. During follow-up, 100% of patients and partners reported high satisfaction with sexual function restoration. Conclusion: IPP implantation is a safe and highly effective treatment for erectile dysfunction, offering excellent complication control and outstanding satisfaction for both patients and partners.